Pengembangan Sistem Informasi Pelaporan pada Korwilker Pendidikan dan Kebudayaan Kecamatan Bareng berbasis Web - Elfa Fatimah; Issa Arwani; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Reporting activities are activities that are commonly found in various agencies, both government agencies, and central agencies. The school reports on school data and student data, which is then sent and recapitulated by the Coordinator for Education and Culture of the Bareng sub-district. The reporting process still uses a manual system, there is no overall system integration. We need a system that can facilitate the reporting process and make monthly recordings that can also provide convenience in managing reporting. Therefore, research was conducted on the Development of a Web-Based Reporting Information System at the Education and Culture Coordinator of the Bareng District. The development of this information system is carried out using the waterfall development method which consists of the stages of needs analysis, system design, implementation, and testing and is developed on a web-based basis. The results of this study obtained 2 actors with 14 functional needs and 1 non-functional need. This system has been tested API using postman, validation testing using the black box method and compatibility testing. In this test, validation tests are carried out on all functional requirements that provide valid results and system compatibility testing can be run well on various browsers and platforms.